2016 IFPRI audited financial statements - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
2016 was another notable year for IFPRI. The institute garnered international recognition, and new research results are informing food and nutrition policy. At COP22 in Marrakech, IFPRI presented projections on the impact of climate change on agriculture and food security derived from IFPRI's IMPACT model. Other modeling work found that the global economic slowdown will slow progress on poverty reduction.